The agrarian reform under the Portuguese revolution, 1974-76: its roots and reversal - Almeida, M. (Studies in People’s History, 2016)
The makers of the Portuguese Revolution of 1974 sought not only the overthrow of a dictatorial regime, but also a reorganisation of Portugal’s economy on new lines, securing control of agriculture and industry in the name of workers. The present paper examines the process of revolutionary agrarian reform in the Alentejo region, a major agricultural zone, and describes how, after the end of the revolutionary period, 1974-76, the reforms of that period were reversed, when the Socialists and Social Democrats successively gained power.